IDENTIFICATION OF PHYSICAL AND SOCIAL POTENTIAL FOR ECOTOURISM DEVELOPMENT IN NEGLASARI VILLAGE, SUKABUMI REGENCY USING REMOTE SENSING AND GEOGRAPHICAL INFORMATION SYSTEMS - Pin, Tjiong Giok; Wibowo, Adi; Alya, Haura Hazema; Nastiti, Afifa Ayu (UI Scholars Hub, 2024)
Identification of physical and social potential needs to be done so that it can be developed as an ecotourism object that has a role in improving the economy of a region. Physical and social potential data can be obtained and interpreted from satellite imagery using remote sensing which is then verified through surveys and direct measurements in the field using GPS and digital maps. Data analysis was performed using the overlay method in GIS. Remote sensing methods using satellite imagery have proven to be superior for obtaining information on an area effectively and sustainably. Landsat imagery 8 and 9 are used to periodically monitor changes in the physical condition of the Neglasari Village area so that they can be used for analysis of the carrying capacity of the environment for ecotourism. The use of the NDVI, NDBI and NDWI algorithms produces suitability for developing ecotourism objects. Attractive and interesting physical and social potential to be developed as an ecotourism object are river channels, hilltops, camping grounds, and agricultural land. All these interesting objects have the potential to support sustainable ecotourism in Neglasari Village.